2012
DOI: 10.3389/fphar.2011.00083
|View full text |Cite
|
Sign up to set email alerts
|

Phorbol 12,13-Dibutyrate-Induced, Protein Kinase C-Mediated Contraction of Rabbit Bladder Smooth Muscle

Abstract: Contraction of bladder smooth muscle is predominantly initiated by M3 muscarinic receptor-mediated activation of the Gq/11-phospholipase C β-protein kinase C (PKC) and the G12/13-RhoGEF-Rho kinase (ROCK) pathways. However, these pathways and their downstream effectors are not well understood in bladder smooth muscle. We used phorbol 12,13-dibutyrate (PDBu), and 1,2-dioctanoyl-sn-glycerol (DOG), activators of PKC, in this investigation. We were interested in dissecting the role(s) of PKC and to clarify the sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 45 publications
5
12
0
Order By: Relevance
“…Inhibition of ROCK by the addition of 1 μM H-1152 significantly decreased force production compared to S1P alone at all time points measured after the addition of S1P (1, 2, and 5 min). Consistent with previous results from our laboratory, inhibition of ROCK tended to decrease baseline force (Wang et al, 2009; Wang et al, 2012), although the H-1152-induced decrease in baseline force was not significant in this set of experiments. The decrease in S1P-induced isometric force production by inhibition of ROCK was significantly greater than that produced by inhibition of PKC.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Inhibition of ROCK by the addition of 1 μM H-1152 significantly decreased force production compared to S1P alone at all time points measured after the addition of S1P (1, 2, and 5 min). Consistent with previous results from our laboratory, inhibition of ROCK tended to decrease baseline force (Wang et al, 2009; Wang et al, 2012), although the H-1152-induced decrease in baseline force was not significant in this set of experiments. The decrease in S1P-induced isometric force production by inhibition of ROCK was significantly greater than that produced by inhibition of PKC.…”
Section: Resultssupporting
confidence: 92%
“…The decrease in S1P-induced isometric force production by inhibition of ROCK was significantly greater than that produced by inhibition of PKC. It is important to note, that previous studies in our laboratory have shown that 3 μM Bis-1 inhibits PKC-dependent pathways and 1 μM H-1152 inhibits ROCK-dependent pathways in rabbit bladder smooth muscle (Wang et al, 2009; Wang et al, 2012). Preliminary studies from our laboratory demonstrated that these two compounds at these concentrations had no effect on MLC phosphorylation levels in a Triton X-100 skinned preparation of rabbit bladder smooth muscle, suggesting Bis and H-1152 have no non-specific effects on the MLC kinase (unpublished results).…”
Section: Resultsmentioning
confidence: 86%
“…However, increased expression of ROCK␤ in c-Rel KO BSM was not associated with increased CPI-17 phosphorylation in the same tissues, suggesting that PKC, rather than ROCK␤, plays a major role in CPI-17 phosphorylation in BSM. This is in agreement with an earlier report that the ROCK isoform that phosphorylates MYPT1 is not involved in in vivo phosphorylation of CPI-17 in BSM (5,39).…”
Section: Nf-b P50 and C-rel Are Required For Cpi-17 Gene Expression Isupporting
confidence: 94%
“…8G; compare the spots for phosphorylated MLC 20 and the graph). Together, these observations suggest that the PKC-mediated BSM contraction that occurs through CPI-17 expression in response to agonist stimulation is independent of MLC 20 phosphorylation, in accordance with earlier observations in rabbit vascular smooth muscle (39,40).…”
Section: Nf-b P50 and C-rel Are Required For Cpi-17 Gene Expression Isupporting
confidence: 92%
“…In addition to the PKC-dependent postjunctional effects of phorbol esters on bladder smooth muscle contraction (Wang et al, 2012), phorbol esters have been found to exert prejunctional effects. Thus, phorbol esters were found to increase [ 14 C]ACh overflow in the rat urinary bladder through a M 1 muscarinic receptor-dependent PKC pathway, with the effects of phorbol esters inhibited by both PKC inhibitors and atropine (Somogyi et al,1997).…”
Section: Introductionmentioning
confidence: 99%